The Planning of LRT for Metro Manila - Santiago, Rene S.
This paper reviews the issues and activities that characterized the planning of the Light Rail Transit system of Metropolitan Manila. A structured approach consisting of five major decision stages is postulated, then applied in discussing the current question: where is the next LRT line? Circumstances and planning methods differed for the two lines. The first one, Taft-Rizal, went ahead somewhat so hurriedly that the normal sequences in the planning process were either compressed or skipped. As a result, some advantages were foregone and unnecessary problems encountered during construction. On the other hand, the planning and feasibility study for Line 2 were conducted on more firmer grounds such as: use of more up to date origin-destination data, examination of alternative alignments, and more comprehensive treatment of a wider range of issues. A radial (Aurora Blvd.) and a circumferential (EDSA) line emerged as having the highest potentials. These two options were then subjected to closer scrutiny, with the Aurora Line coming out on top. However, information gaps still remain to cast doubts on the advisability of pursuing the project at an early date. A decision in favor of the Aurora Line will entail a government investment of US220 million. The project's magnitude and impact are such that further studies can be justified-if only to address the affordability issue, the preparation of detailed engineering works, and the sourcing of subsidy, among others.